Structural Transformation and Income Distribution: Kuznets and Beyond - Ravi Kanbur (Institute of Labor Economics (IZA), 2017)
This paper explores the question of structural transformation and income distribution through the eyes of the pioneer in such analysis, Simon Kuznets. It argues that his 1955 paper stands the test of time in providing insights which are relevant to understanding current phenomena like the evolution of Chinese inequality. The paper shows how the Kuznetsian framework can be used, for example, in predicting the differential relationship between urbanization and inequality in India versus China, in assessing the detail of the contribution of sectoral mean and inequality evolution to overall inequality change, and in linking the recent inequality of opportunity literature to rural-urban migration. Thus the original Kuznets framework has the seeds of getting us beyond Kuznets as sometimes (mis)understood in the literature on structural transformation and income distribution.
Keywords: O41; O14; D31; 330; Kuznets curve; inequality and development; rural-urban migration; Chinese inequality; place of birth and equality of opportunity